Experiential Learning (El): An Effective Teaching Method To Construct Studentsâ Writing Skill Viewed From Self-Efficacy - Meitikasari, Ani (Proceeding of International Conference on Teacher Training and Education, 2016)
This study investigates the effects of Experiential Learning in teaching writing from the perspective ofstudentsâ self-efficacy by means of a comparative experiment concerning on the experimental group taughtby Experiential Learning and the control group by using Direct Instruction. The sixty students of a seniorhigh school in Central Java, Indonesia were chosen randomly and participated in this research. Theseparticipants are asked to compose a text in order to examine their writing skill after having eight-meetingtreatments and fulfil the self-efficacy questionnaire. The results show that Experiential Learning guides thestudents to achieve significantly a greater writing skill than those using Direct Instruction and the high selfefficaciousstudents perform better writing skill than those having low self-efficacy. Additionally, it wasfound that there is an interaction between those methods and students self-efficacy in writing skill. Therefore,Experiential Learning is suggested as an alternative teaching method in constructing studentsâ writing skilland self-efficacy.